THE ACADEMIC PROCRASTINATION IN STUDENTS AND HOW TO OVERCOME IT - Sastri, Prinska Damara (Journal of Business and Management Inaba, 2022)
This scientific work aims to determine the description of academic procrastination in students. This scientific work was made using a literature study method that uses the results of existing written works or research by conducting analysis or review to obtain research data. This scientific work examines 11 research journals related to academic procrastination with different subjects and approaches. The results showed that academic procrastination in students was fairly high, with underlying factors such as internal and external factors. Furthermore, the training techniques that can be done are self-management training and cognitive restructuring techniques. The training can be done to reduce the habits that make students academic procrastination.